2015
DOI: 10.1371/journal.pone.0121700
|View full text |Cite
|
Sign up to set email alerts
|

Lancet Dynamics in Greater Horseshoe Bats, Rhinolophus ferrumequinum

Abstract: Echolocating greater horseshoe bats (Rhinolophus ferrumequinum) emit their biosonar pulses nasally, through nostrils surrounded by fleshy appendages (‘noseleaves’) that diffract the outgoing ultrasonic waves. Movements of one noseleaf part, the lancet, were measured in live bats using two synchronized high speed video cameras with 3D stereo reconstruction, and synchronized with pulse emissions recorded by an ultrasonic microphone. During individual broadcasts, the lancet briefly flicks forward (flexion) and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…Evidence from several sources supports the hypothesis that the shape changes in the biosonar interfaces play a functional role: (i) the shape changes are effected by elaborate muscular actuation mechanisms [16,19], (ii) bats control the dynamic shape configuration sequences based on behavioral context [14,16], (iii) shape deformations coincide with ultrasonic diffraction in time [14,15], (iv) the magnitudes of the shape changes are significant compared to the transmitted wavelength [14,15,17]. In accordance with (iv), noseleaf and pinna deformations in horseshoe bats have been predicted to produce qualitative beampattern changes [15,17,20]. Similar changes have been demonstrated experimentally with biomimetic reproductions of noseleaves [21] and pinnae [10,22].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Evidence from several sources supports the hypothesis that the shape changes in the biosonar interfaces play a functional role: (i) the shape changes are effected by elaborate muscular actuation mechanisms [16,19], (ii) bats control the dynamic shape configuration sequences based on behavioral context [14,16], (iii) shape deformations coincide with ultrasonic diffraction in time [14,15], (iv) the magnitudes of the shape changes are significant compared to the transmitted wavelength [14,15,17]. In accordance with (iv), noseleaf and pinna deformations in horseshoe bats have been predicted to produce qualitative beampattern changes [15,17,20]. Similar changes have been demonstrated experimentally with biomimetic reproductions of noseleaves [21] and pinnae [10,22].…”
mentioning
confidence: 89%
“…In recent years, a growing body of evidence has accumulated to suggest that, beyond their static geometric complexity, the noseleaves and pinnae of horseshoe bats have a prominent dynamic dimension [11]. Fast dynamic shape changes that go beyond rotations of static shapes [12,13] have been demonstrated to occur in both interface structures, noseleaves [14,15] and pinnae [16,17]. Along with the dynamic changes to the interface shapes, changes to the emission beampatterns during natural biosonar behaviors have been reported, but the underlying acoustic mechanisms remain unclear [18].…”
mentioning
confidence: 99%
“…Hence, these motions could change the acoustic characteristics of the biosonar emission and reception during a single pulse or a single echo. Indeed, such changes have been predicted by numerical analysis (Gao et al 2011;He et al 2015) and demonstrated with biomimetic physical prototypes Fu et al 2016). Time variant acoustic characteristics would allow the bats to sense their environments through "multiple views" and hence could enhance the quantity -and perhaps also the quality -of the sensory information available to the animals.…”
Section: Dynamic Information Encoding: Noseleaf and Pinna Motionsmentioning
confidence: 97%
“…These shape changes are driven by specialized musculatures (Schneider and Möhres 1960;Schneider 1961;Göbbel 2002) and are known to occur during pulse emission (for the noseleaf (Feng et al2012;He et al 2015)) or echo reception (for the pinnae (Yin et al 2015)). Noseleaf and pinna motions are fast and occur on a similar time scale as the durations of the biosonar pulses and echoes (Gao et al 2011;Feng et al 2012;He et al 2015). Hence, these motions could change the acoustic characteristics of the biosonar emission and reception during a single pulse or a single echo.…”
Section: Dynamic Information Encoding: Noseleaf and Pinna Motionsmentioning
confidence: 99%
“…1). Similar to the furrows in the noseleaf of the greater horseshoe bat (He et al, 2015), the furrow of Asellicus stoliczkanus is one part of the noseleaf and not adjacent to the nostrils. The furrows of Aselliscus Stoliczkanus play an important role in distinguishing them from other species of bats (Koopman, 1994).…”
Section: Introductionmentioning
confidence: 94%